Singular perturbation analysis of free-time optimal control problems - KAO, Y. K.; BANKOFF, S. G. (International journal of systems science, 1974)
The singular perturbation theory for free-time optimal control problems is developed, introducing a scaling parameter as an additional parameter, and then extended to eontrol-mequality constraints.